Pengaruh Pemberian Jenis Murbei Morus multicaulis dan Morus cathayana Terhadap Produksi Kokon Ulat Sutera (Bombyx mori L.) Varietas Lokal, Jepang, Cina dan Rumania - . Hartati; . Umar (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFThe study has been conducted to determine whether there are influences and interactions of type of mulberry Morus multicaulis and Morus cathayana to cocoon production in the silkworm (Bombyx mori L.) Local varieties, Japan, China and Rumania. Study was arranged in Complete Randomized Design (CRD), with a factorial design of two types of mulberry leaf with four varieties of silkworms with three replications. The treatments combination were 24 treatments. The parameters of this research included cocoon weight, cocoon leather weight, fiber length and fiber weight. The results showed that Morus cathayana have cocoon 1.188 g weight, cocoon skin 0.214 g, 1015.027 m of fiber length and fiber weight 0.218 g in silkworm Romania variety (A2B4), when compared with Morus multicaulis produced cocoon weight as 1.143 g, and cocoon skin 0.197 g, fiber length 944.745 m, and fiber weight 0.199 g in silkworm Romania variety (A1B4). Therefore after data were analyzed with LSD (α=0.05) Morus multicaulis and Morus cathayana to silkworm Local, Japan, China and Romania and the interactions between mulberrys with four varieties of silkworm cocoons have real impact on weight, heavy leather cocoon and fiber length and weight of fiber produced. Key words: Morus multicaulis, Morus cathayana, production of silk cocoon, silkworm